1990
DOI: 10.1002/path.1711620309
|View full text |Cite
|
Sign up to set email alerts
|

cerbB2 oncogene expression in ovarian cancer

Abstract: One hundred and four common epithelial malignancies of the ovary were stained for c-erbB-2 using an affinity-purified polyclonal antibody 21N. Twenty-three out of 104 (22.1 per cent) showed cytoplasmic staining alone. Nine out of 104 (8.7 per cent) showed both membrane and cytoplasmic staining. In a multivariate Cox analysis with other known risk factors the relative risk for cytoplasmic staining alone was 1.456 (chi 2 = 1.71, P greater than 0.1) and for membrane and cytoplasmic staining 0.316 (chi 2 = 7.95, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 13 publications
6
18
1
2
Order By: Relevance
“…The proportion of tumors showing a definite immunostaining for HER2/neu protein (scores 2+/3+) was similar to the percentages of immunostaining reported in previous studies [13, 18, 19, 20]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The proportion of tumors showing a definite immunostaining for HER2/neu protein (scores 2+/3+) was similar to the percentages of immunostaining reported in previous studies [13, 18, 19, 20]. …”
Section: Discussionsupporting
confidence: 72%
“…Like other authors [13, 18, 19, 20, 21], we also found no statistical correlation between HER2/neu protein overexpression and age, histological subtype, or residual tumor, nor did we find any relationship between overexpression and FIGO stage, confirming that activation of HER2/neu overexpression can occur both in early and late stages of disease [22, 23]. …”
Section: Discussionsupporting
confidence: 68%
“…Berchuck et al 34 reported a poorer prognosis for OC patients in whom HER-2 was overexpressed, in contrast to Haldane et al and Rubin et al, 11,35 who did not find any adverse prognostic significance on survival for HER-2 overexpression. Buller et al 36 analyzed 11 familial OC patients and found that 6 of the patients with tumors that were negative for HER-2 had a prolonged 5-year survival rate of 67% in comparison with a 5-year survival rate of 17% in the patients with nonfamilial OC.…”
Section: Discussionmentioning
confidence: 93%
“…In breast and ovarian cancers localisation of the epidermal growth factor (EGF) receptor status and HER-2/neu oncogene product have been shown to correlate well with survival (Sainsbury, 1987;Haldane et al, 1990). These factors are primarily thought to reflect differences in proliferation rates of the tumours, and are not directly related to the mechanism of action of any specific agent used in their treatment.…”
mentioning
confidence: 99%